HIV-1 viral escape in cerebrospinal fluid of subjects on suppressive antiretroviral treatment - Edén, Arvid; Fuchs, Dietmar; Hagberg, Lars; Nilsson, Staffan; Spudich, Serena; Svennerholm, Bo; Price, Richard W; Gisslén, Magnus (The Journal of infectious diseases, 2010)
Occasional cases of viral escape in cerebrospinal fluid (CSF) despite suppression of plasma human immunodeficiency virus type 1 (HIV-1) RNA have been reported. We investigated CSF viral escape in subjects treated with commonly used antiretroviral therapy regimens in relation to intrathecal immune activation and central nervous system penetration effectiveness (CPE) rank. Sixty-nine neurologically asymptomatic subjects treated with antiretroviral therapy >6 months and plasma HIV-1 RNA <50 copies/mL were cross-sectionally included in the analysis. Antiretroviral therapy regimens included efavirenz, lopinavir/ritonavir or atazanavir/ritonavir combined with tenofovir, abacavir, or zidovudine and emtricitabine or lamivudine. HIV-1 RNA was analyzed with real-time polymerase chain reaction assays. Neopterin was analyzed by enzyme-linked immunosorbent assay. Seven (10%) of the 69 subjects had detectable CSF HIV-1 RNA, in median 121 copies/mL (interquartile range, 54-213 copies/mL). Subjects with detectable CSF virus had significantly higher CSF neopterin and longer duration of treatment. Previous treatment interruptions were more common in subjects with CSF escape. Central nervous system penetration effectiveness rank was not a significant predictor of detectable CSF virus or CSF neopterin levels. Viral escape in CSF is more common than previously reported, suggesting that low-grade central nervous system infection may continue in treated patients. Although these findings need extension in longitudinal studies, they suggest the utility of monitoring CSF responses, as new treatment combinations and strategies modify clinical practice.